Comparative Distribution, Correlation, and Chemometric Analyses of Selected Metals in Scalp Hair of Angina Patients and Healthy Subjects - Ilyas, Asim; Ahmad, Hamad; Shah, Munir H. (Biological trace element research, 2015)
Numerous epidemiological studies are preponderance of evidences intimating development of coronary artery disease caused by metal imbalance. The present study was aimed to analyze Ca, Cd, Cr, Cu, Fe, K, Mg, Mn, Na, Pb, Sr, and Zn in the scalp hair of angina patients and healthy subjects/controls employing HNO 3 –HCLO 4 -based wet digestion followed by quantification with atomic absorption spectrophotometry. The average concentrations of Cd, Cu, Cr, Fe, Mn, Pb, and Sr revealed significantly higher levels in scalp hair of patients than controls; however, Na and Zn were appreciably higher in healthy subjects. Dissimilarity in the trace metal distribution was also observed with gender, residence, dietary habits, and smoking habits of both donor groups. The correlation study and multivariate analyses revealed diverse mutual relationships and apportionment of the trace metals in the scalp hair of patients and controls.